Farmers’ perceptions of climate change and adoption of climate-smart agriculture practices in Nyando Basin, Kenya - Musyimi, Anthony (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
This Info Note summarizes findings of the research project, “Using Climate-Smart Financial Diaries for Up-scaling in Nyando, Western Kenya,” led by the Amsterdam Center for World Food Studies (ACWFS) with participation of the CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) in East Africa, the University of Nairobi’s School of Economics and Wageningen Economic Research. The findings are based on baseline data of an on-going bigger panel study involving 122 households from 44 villages in Kericho and Kisumu Counties that compose the Nyando Basin. The study aims to inform how to improve farmers’ response to climate variability, food security and household income. The data was collected in 2019 by graduate students from the University of Nairobi.